Design, learning networks and service innovation. (March 2018) - Carvalho, Lucila; Goodyear, Peter
Abstract : This paper has three main aims. It argues that education is a surprisingly neglected sector of activity in research on service design and innovation and that greater attention to education as a service can shed new light on theoretical and methodological issues in service design and innovation research. It shows how a novel reframing of education activity – as networked learning – can enrich some critical areas of thinking about the analysis, design and evolution of co-produced services more generally. Finally, it identifies a family of participatory design approaches that are particularly well-tuned to the needs of service innovation. The paper shows how contemporary ideas on individual, group and network-wide learning can benefit research on services and service innovation. Highlights: Education is a fruitful and neglected sector for research on service design and service innovation Analysing services as learning networks illuminates core service research issues Co-production of services mobilises heterogeneous networks of people and things Endogenous service innovation and enhancement involves collaborative learning